Analysis of Demand Responsive Pelican Crossing in Mixed Traffic Conditions. (2017) - Yulianto, Budi; Setiono,
Abstract: Demand responsive Pelican Crossing has been used widely at midblock pedestrian crossing. However this controller has not been tested in mixed traffic conditions, where the traffic streams are heterogeneous, lack of lane discipline and high proportion of motorcycles. This paper describes an evaluation of the performance of demand responsive Pelican Crossing using Extension Principle (PC VAC-EP) under mixed traffic conditions. An investigation was carried out to find the most appropriate extension time for the PC VAC-EP that was suitable for mixed traffic. The best performance of the PC VAC-EP was, then, compared with the Pelican Crossing Conventional (PC C) on validated simulated pedestrian crossing. The effectiveness of the proposed PC VAC-EP and PC C were evaluated by the simulation program VISSIM.